Pengembangan Digital Motion Comic Berfokus pada Autentikasi Mitologi, Studi Kasus: “Ragnarok” - Suciadi, Marcellinus Ferdinand; Andre, Andre; Novelinda, Levina (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2020)
Abstract—Norse Mythology is a mythology that originated in the Scandinavian region, which is the basis of all mythologies in the area. At this time, people's knowledge of Norse mythology was only obtained from films, and the adaptation was not in accordance with the original mythology. Submission of stories remains inauthentic due to additional characters that are not present in the original story, thus affecting the authentication of the mythology being conveyed. To educate the public about Norse mythology, interesting media are needed but can also convey a message by not changing the specific elements of the mythology. The survey was conducted on 53 teen respondents and fans of the Marvel franchise. From the survey results, 88% of respondents had never used a motion comic application, but were interested in trying a motion comic application. Through the survey results, a motion comic with the theme of Norse Mythology was made to fulfill the stated goals. The results of the design will be implemented and have several options, including Starting Story, Journal, and Credit. Start Story will start the story from beginning to end, with a mini game in the middle. The journal is a collection of information about the Ragnarok War, and the Credit contains the names of those who intervened in making the Ragnarok motion comic. The making of this motion comic uses several programs. The verification and validation stage is carried out after the implementation has been completed. This application can help teens and adults to understand the mythological story of the Ragnarok War, based on the results of the validation that has been done. Keywords: motion comic, mythology, Norse, Ragnarok, war Abstrak—Mitologi Nordik merupakan mitologi yang berasal dari daerah Skandinavia, yang merupakan dasar dari segala mitologi yang berada pada daerah tersebut. Pada masa ini, pengetahuan masyarakat mengenai mitologi Nordik hanya didapat dari film, dan adaptasi tersebut tidak sesuai dengan mitologi aslinya. Penyampaian cerita tetap tidak autentik dikarenakan adanya karakter tambahan yang tidak ada dalam cerita aslinya, sehingga mempengaruhi autentikasi mitologi yang disampaikan. Untuk mengedukasi masyarakat mengenai mitologi Nordik, maka dibutuhkan media yang menarik namun juga dapat menyampaikan suatu pesan tersebut dengan tidak mengubah unsur khas dari mitologi tersebut. Survei dilakukan kepada 53 responden remaja dan fans dari franchise Marvel. Dari hasil survey, 88% responden belum pernah menggunakan aplikasi motion comic, namun tertarik untuk mencoba aplikasi motion comic. Melalui hasil survei tersebut, dibuatlah sebuah motion comic bertema Mitologi Nordik untuk memenuhi tujuan yang telah ditetapkan. Hasil desain akan diimplementasikan dan memiliki beberapa pilihan, diantaranya adalah Mulai Cerita, Jurnal, dan Kredit. Mulai Cerita akan memulai cerita dari awal hingga akhir, dengan mini game di tengah-tengah. Jurnal adalah kumpulan dari informasi mengenai Perang Ragnarok, dan Kredit berisi nama-nama pihak yang turut campur tangan dalam pembuatan motion comic Ragnarok. Pembuatan motion comic ini menggunakan beberapa program. Tahap verifikasi dan validasi dilakukan setelah implementasi telah selesai. Aplikasi ini dapat membantu remaja dan dewasa untuk memahami cerita mitologi Perang Ragnarok, berdasarkan hasil validasi yang telah dilakukan. Kata kunci: mitologi, motion comic, norse, perang, ragnarok